2004
DOI: 10.1111/j.1467-7687.2004.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Early development of subcortical regions involved in non‐cued attention switching

Abstract: This study examined the cognitive and neural development of attention switching using a simple forced-choice attention task and functional magnetic resonance imaging Fourteen children and adults made discriminations among stimuli based on either shape or color. Performance on these trials was compared to performance during blocked trials requiring all color or all shape discriminations. Magnetic resonance echo planar images were acquired during performance of the task. Both children and adults showed robust bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 80 publications
(97 reference statements)
8
66
0
Order By: Relevance
“…These results are consistent with previous developmental imaging studies, which have reported early recruitment of the caudate in attention switching but late development of cortical areas (Casey et al, 2004). Thus, despite reports showing that the caudate has a slow structural developmental trajectory (Giedd, 2008), this study and others (Casey et al, 2004) report early functional involvement of the caudate. The results of the current study possibly indicate that brain areas that are responsive to positive performance feedback in adults function at adult level earlier than brain areas that are responsive to negative performance feedback in adults.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with previous developmental imaging studies, which have reported early recruitment of the caudate in attention switching but late development of cortical areas (Casey et al, 2004). Thus, despite reports showing that the caudate has a slow structural developmental trajectory (Giedd, 2008), this study and others (Casey et al, 2004) report early functional involvement of the caudate. The results of the current study possibly indicate that brain areas that are responsive to positive performance feedback in adults function at adult level earlier than brain areas that are responsive to negative performance feedback in adults.…”
Section: Discussionsupporting
confidence: 82%
“…12 Such variability is likely to arise secondary to the normal maturation of frontoparietal networks underlying spatial working memory from childhood to adolescence. 33,34 Nonetheless, the task was highly sensitive in terms of functional brain imaging. All children were clearly engaged in the task, performing above chance level, and fMRI consequently revealed significant activation patterns associated with this task performance.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Casey et al [2002] showed increased left middle frontal activation in adults, but increased volumes of activation in hippocampal/parahippocampal and basal ganglia in children. The only study, to our knowledge, that has investigated cognitive inhibition in the context of task switching found in-creased activation in adults compared with children in frontal and parietal brain regions [Casey et al, 2004].…”
Section: Introductionmentioning
confidence: 99%